The effects of syntactic and lexical complexity on the comprehension of elementary science texts - Diana J. Arya; Elfrieda H. Hiebert; P. David Pearson (International Electronic Journal of Elementary Education, 2017)
In this study we examined the effects of syntactic and lexical complexity on third-grade students' comprehension of science texts. A total of 16 expository texts were designed to represent systematic differences in levels of syntactic and lexical complexity across four science-related topics (Tree Frogs, Soil, Jelly Beans and Toothpaste). A Latin-square design was used to counterbalance the order of administration of these 16 texts. After reading each text, students responded to a post-test comprehension measure (without access to the text). External measures of reading achievement and prior vocabulary knowledge were also gathered to serve as control variables. Findings show that lexical complexity had a significant impact on students' comprehension on two of the four topics. Comprehension performance was not influenced by the syntactic complexity of texts, regardless of topic. Further, no additional effects were found for English language learners. Potentially moderating and confounding issues, such as the inference demand of syntactically simple texts and the role of topic familiarity, are discussed in order to explain the inconsistency of the findings across topics.